Integrating children ́s values in policymaking: Challenges and opportunities in a diverse society - Murcia Alvarez, E.; Ramos, A.; Tendais, I.; Rodrigues, R. B. (Actas del VIII Congreso de la Red Española de Política Social (REPS), 2021)
Values are a central dimension of human social life, they are core to a person’s self-concept and identity and drive individual actions towards both personal enhancement and social transformation. At a social level, values govern how individuals relate to others and shape the organization of societies being, therefore, powerful guidelines to face new societal challenges like inclusion/exclusion issues, social justice or cultural diversity. Research with adults in this field has demonstrated that human values are powerful predictors of a wide range of behaviours, attitudes and beliefs. However, research with children is still very recent and has mostly focused on adolescents and older children, probably due to concerns about young children's capabilities to produce reliable information and discourse. In the same way, children's voices regarding political issues have been frequently dismissed even when children's right to participate fully in political and cultural life is specifically recognized in the United Nations Convention on the Rights of the Child. Therefore, giving voice to children is ultimately a matter of respecting their rights. To address this gap we introduce in this presentation a project that seeks to respond to this need by mapping the basic human values (e.g. Schwartz, 1992) of children and young adolescents (6 to 14 years) and its associations with the representations of justice and attitudes towards different social groups. Also, we intend to propose further directions to incorporate values and children’s views in education policies and decision-making.